Quality Deterioration of Spent Hen Jerky Packed Using Different Packaging Methods and Stored at Ambient Temperature - Sorapukdee , Supaluk; Uesakulrungrueng, Chanpen (International Journal of Poultry Science, 2018)
Background and Objective: The packaging system of jerky, a semi-dried meat product, is one of the most important factors controlling product deterioration during prolonged storage, especially in the case of spent hen meat, which is susceptible to oxidation. This typical product is generally packed in vacuum (VAC) packaging or via heat sealing with an oxygen scavenger (HSOS). This study aimed to determine the suitable packaging and to assess the physicochemical, microbiological and sensory qualities of spent hen jerky packed using different packaging methods (VAC vs. HSOS) over 90 days of storage. Methodology: The jerky was prepared by grinding spent hen meat and mixing it with ingredients, followed by forming, dehydrating and roasting the jerky. The resulting products were randomly packed under VAC or via HSOS and stored at 32±2°C for 90 days. The changes in the physicochemical and microbiological qualities of the packed products were determined at 15 days intervals, while the changes in the sensory qualities were evaluated at 90 days by comparison with freshly prepared product (0 day) as a control. Results: The moisture content and water activity of the jerky increased with the storage period (p0.05). Thiobarbituric Acid Reactive Substances (TBARS) increased in samples during storage (p